Traditional Homegardens in Rural Landscapes of Northeast India – A Model for Conserving Plant Species for Sustainability - Tangjang, Sumpam; Arunachalam, A. (Indian Journal of Hill Farming, 2018)
Call for natural resources management, biodiversity and environmental conservation related subjects are gaining momentum. Conservation scientists, researchers, Non- Governmental Organizations (NGOs) and policy makers are trying to address these issues from local to global levels in all possible ways. In contrast to the present global scenario, the rural folks in the remote tribal inhabited northeast India are, however, silently conserving natural resources and are achieving sustainable agriculture with their rich Indigenous Knowledge Systems (IKS). The study was carried out considering the role of plant species in traditional homegardens for sustainability in Itanagar, Arunachal Pradesh and North Lakhimpur, Assam, two neighbouring Indian states located in the Eastern Himalayas. We recorded 79 plant species belonging to 46 botanical families presenting a multi-tier canopy configuration with intimate mixture that provides a wide ranges of services such as folk medicine, construction material, timber, valuable food sources, cashincome, etc. Rice and arecanut were identified as important cultural as well as cash-crops in North Lakhimpur while the farmers’ in Itanagar prefers more timber species. The analysis of existing management regime, however, indicates that the local practitioners lack modern scientific knowledge and still follow traditional management systems. The study also reveals that traditional homegardens can be a valuable tool for in situ conservation of plant species and maintaining ecosystem functioning.